2017
DOI: 10.1097/gox.0000000000001501
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Regression of Lymphangiomas in a Single Center Over 34 Years

Abstract: Background:A lymphangioma, also called a lymphatic malformation, is a congenital condition that frequently occurs in young children. It is classified into 3 groups depending on the size of the cysts (macrocystic, microcystic, and mixed). Spontaneous regression occurs in some cases; however, the characteristics of patients who show regression have not been studied previously. Furthermore, the types and the timing of the initial treatment are still controversial. Therefore, we statistically analyzed the occurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 25 publications
3
28
0
Order By: Relevance
“…Regression of lymphangiomas may also occur after an infection 22. In the largest series published on lymphangiomas, Kato et al reported that among 153 patients, spontaneous regression only occurred in macrocystic or mixed-type lymphangiomas and in older patients that were more than 2 years of age 23. It must be noted however that none of the patients in this particular study had intra-abdominal lymphangiomas.…”
Section: Discussionmentioning
confidence: 58%
“…Regression of lymphangiomas may also occur after an infection 22. In the largest series published on lymphangiomas, Kato et al reported that among 153 patients, spontaneous regression only occurred in macrocystic or mixed-type lymphangiomas and in older patients that were more than 2 years of age 23. It must be noted however that none of the patients in this particular study had intra-abdominal lymphangiomas.…”
Section: Discussionmentioning
confidence: 58%
“…Based on our previous report, macrocystic and mixed-type LMs had a good possibility of regression within 3 months from their initial onset. 4 Because the presented case showed a gradual enlargement over 7 years, spontaneous regression could not be expected.…”
Section: Discussionmentioning
confidence: 83%
“…According to the 2018 International Society for the Study of A Case of Pancreatic Lymphangioma J Curr Surg. 2021;11(1): [24][25][26][27] Vascular Anomalies, cystic lymphangioma is also referred to as macrocystic lymphatic malformation (> 1 cm mean diameter), and cavernous lymphangioma is also referred to as microcystic lymphatic malformation (< 1 cm mean diameter). Therefore, lymphangiomas can be classified into microcystic, macrocytic and mixed lymphangiomas [18].…”
Section: Discussionmentioning
confidence: 99%